Field Research Project: India's Agro-Meteorological Advisory Service Program - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
By the end of this study, led by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), a total of 18 villages in six states across India’s main agro-climate zones will have been sampled, for a total of 900 farmers interviewed – half of whom will be women farmers. In each village, separate focus groups of men and women farmers are interviewed, to delve into the equity challenges in reaching the most vulnerable farmers with agro-meteorological advisories. One of the specific interests of this study is to derive best practices in delivering salient farmer-focused climate services, as well as areas for improvement, for the consideration of other countries across CCAFS target areas where such weather-based agricultural support services have not yet taken off.